2019
DOI: 10.3390/en12142680
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of Pulverized-Fuel Jet Flames That Apply Large Amounts of Excess Air—Implications for NOx Formation

Abstract: Measures to reduce nitrogen oxides (NOx) formation in industrial combustion processes often require up-scaling through pilot-scale facilities prior to being implemented in commercial scale, and scaling is therefore an important aspect of achieving lower NOx emissions. The current paper is a combined experimental and modelling study that aims to expand the understanding of constant velocity scaling for industrial jet flames applying high amounts of excess air. These types of flames are found in e.g., rotary kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…As has been previously observed, 20 NO x emissions are significantly higher in pilot-scale than in full-scale. Replacing the reference burner with the precessing jet burner in pilotscale reduced NO x by 14% in Hood A and ∼17% in Hood B.…”
Section: Summary Of Investigated Measuressupporting
confidence: 81%
See 3 more Smart Citations
“…As has been previously observed, 20 NO x emissions are significantly higher in pilot-scale than in full-scale. Replacing the reference burner with the precessing jet burner in pilotscale reduced NO x by 14% in Hood A and ∼17% in Hood B.…”
Section: Summary Of Investigated Measuressupporting
confidence: 81%
“…The discussion on NO x control in iron-ore rotary kilns starts at the conclusion from our previous work, based mostly on the FlexiFuel 7 campaign, that the net conversion of char-N to NO is responsible for the high NO x emissions. Our simulations (using the same model as in this Article) showed that the large amounts of air expose the char particles to high partial pressures of oxygen and reduce the concentrations of NO and char by dilution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Standard ILC calciners lack a combustion chamber; the body's average oxygen content is between 8 and 10%. Any energy from combustion that is present in the calciner body is promptly consumed by meal, thus limiting access to the required oxygen [58].…”
Section: Location Of Burnersmentioning
confidence: 99%